Educators perceptions of implementing environment-based character education: Evidence from Landak Region - Carla Hermanussen; Dian Febrianti; Mustika Aji Hertanto (Education and Development Research, 2025)
Global crises, particularly the climate crises, highlight the urgent need for educational approaches that cultivate environmental responsibility. The aim of this study is to explore how educators in Landak Region, West Kalimantan, perceive the importance, adequacy, barriers, and success factors of Environment-Based Character Education (EBCE). A questionnaire-based survey was conducted, combining closed and open-ended items, and data were analyzed through descriptive statistics, thematic coding, t tests, chi-square tests, and Spearman correlations. The results show that concern about the climate crises is consistently high across demographic groups, yet EBCE integration into school practice remains fragmented and limited. Barriers include insufficient teacher training, lack of resources, and weak institutional support, while success factors include project-based learning, digital tools, cross-subject integration, and community collaboration. The findings imply that EBCE holds considerable potential for strengthening sustainable education if supported by coherent policies, institutional commitment, and investment in teacher capacity. The study improves existing knowledge by linking local cultural strengths with national frameworks and by offering evidence-based insights for more effective EBCE implementation.